Setup errors in radiation therapy for thoracic tumor patients of different body mass index. (1st March 2018) - Zhao, Jin; Zhang, Mingyun; Zhai, Fushan; Wang, Haiyan; Li, Xingde
Abstract: Purpose: To assess the setup errors in radiation therapy for thoracic tumors patients of different somatotypes, and to seek an individualized mathematical basis for defining the planning target volume (PTV). Methods: Sixty patients with thoracic tumors were divided into four somatotypes according to their body mass index (BMI), and their body positions were setup by two groups of technicians independently. CT simulations were performed and the reconstructed radiography was digitally generated as reference images for location verification and error measurement. By setting positioning error ranges, the within‐range positioning correction rate was compared among groups. Results: Position setups for patients in the emaciated group, moderate group, and overweight group were relatively stable (with minor setup error differences between the two groups of technicians). In emaciated group, moderate group, overweight group, and obese group, setup errors in the right–left direction (R‐L) were 2.2 ± 1.3 mm, 2.2 ± 1.6 mm, 3.9 ± 3.1 mm, and 8.8 ± 3.5 mm, respectively; whereas the setup errors in the four groups in the superior–inferior(S‐I) direction were 2.4 ± 1.8 mm, 2.1 ± 1.9 mm, 3.2 ± 2.6 mm, and 5.4 ± 3.5 mm, and in the anterior–posterior (A‐P) direction were 2.2 ± 1.7 mm, 1.9 ± 1.9 mm, 3.2 ± 2.9 mm, and 6.2 ± 4.2 mm, respectively. Moreover, in the moderate group, the positioning correction rate in the three directions (R‐L, S‐I, and A‐P) was 20%, 9%, 8% within the error range of 5–10 mm, and 3%, 0%, 1% with a more than 10 mm error range. However, in overweight group and obese group, the positioning correction rate in these three directions (also with a more than 10 mm error range) was 23%, 27%, 19% and 21%, 16%, 23%, respectively. Conclusions: In radiation therapy for patients with thoracic tumors, the definition of PTV should be individualized. Meanwhile, with the increase in BMI, positioning correction rate has a tendency to rise too.